Endoscopic management of idiopathic subglottic stenosis in pregnancy. (December 2021) - Kanzara, Todd; Rotman, Anthony; Kinshuck, Andrew; Al Yaghchi, Chadwan; Tan, Min Yi; Yu, Christina; Sandu, Guri
Aims: To describe the use of laser, endoscopic balloon dilatation with jet ventilation anaesthesia in the treatment of pregnant women with idiopathic subglottic stenosis. Materials and methods: This is a case review of pregnant women with idiopathic subglottic stenosis, presenting to a tertiary referral centre with worsening breathlessness. Data were extracted from patient case notes. Results: Four women underwent surgical management of subglottic stenosis in pregnancy. One patient required two procedures during the course of their pregnancy due to restenosis. All women had improvement in symptoms post-operatively and went on to deliver healthy babies at term. Conclusion: Endoscopic balloon dilatation of idiopathic subglottic stenosis is a safe and viable treatment option in pregnancy and should be offered as first-line treatment in symptomatic women.